2009
DOI: 10.1002/jnr.22060
|View full text |Cite
|
Sign up to set email alerts
|

CD38 regulation in activated astrocytes: Implications for neuroinflammation and HIV‐1 brain infection

Abstract: Reactive astrogliosis is a key pathological aspect of neuroinflammatory disorders including human immunodeficiency virus type 1 (HIV-1)-associated neurological disease. On the basis of previous data that showedastrocytes activated with interleukin (IL)-1beta induce neuronal injury, we analyzed global gene changes in IL-1beta-activated human astrocytes by gene microarray. Among the up-regulated genes, CD38, a 45-kDa type II single chain transmembrane glycoprotein, was a top candidate, with a 17.24-fold change t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 56 publications
(71 reference statements)
2
46
1
Order By: Relevance
“…Microglia and astrocytes maintain homeostasis within the CNS during health; however, they also mediate very specific disease mechanisms as illustrated in Alexander's disease in which GFAP polymorphisms result in demyelination, neurodegeneration, and delayed development (56,57) or HIV-associated encephalopathy during which microglia/macrophages and astrocytes are infected by HIV-1, resulting in neuroinflammation with axonal loss (58,59). Hence it is plausible that a retroviral env-encoded glycoprotein such as Syncytin-1 might induce ER stress and inflammation in glia, which results in impaired myelin homeostasis and limited remyelination postinjury.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia and astrocytes maintain homeostasis within the CNS during health; however, they also mediate very specific disease mechanisms as illustrated in Alexander's disease in which GFAP polymorphisms result in demyelination, neurodegeneration, and delayed development (56,57) or HIV-associated encephalopathy during which microglia/macrophages and astrocytes are infected by HIV-1, resulting in neuroinflammation with axonal loss (58,59). Hence it is plausible that a retroviral env-encoded glycoprotein such as Syncytin-1 might induce ER stress and inflammation in glia, which results in impaired myelin homeostasis and limited remyelination postinjury.…”
Section: Discussionmentioning
confidence: 99%
“…Both connexin and nucleoside transporters are also present in the organellar membranes and can perform similar functions for the type-II CD38 that is intracellular (reviewed in [138,139]). Indeed, it is well documented that CD38 is, by no means, a purely surface protein, but is expressed also in organelles [144][145][146], including the nucleus [147][148][149].…”
Section: Membrane Topology and Regulation Of Cd38mentioning
confidence: 99%
“…IL-1-activated astrocytes are known to release cytokines like IL-6 and chemokines like CCL2, CXCL8 and RANTES (Lee and Aarhus, 1993;Zhao and Brinton, 2004;Sharma et al, 2007). Our work showed that CD38 is a partial regulator of chemokine and cytokine signaling by IL-1-activated astrocytes, thus affecting the inflammatory milieu during HIVE (Kou et al, 2009). IL-1 has also been shown to mediate activation of mitogen activated protein kinases (MAPKs) in primary astrocyte cultures (Parker et al, 2002;.…”
Section: Neuroinflammation During Hive and Astrocytesmentioning
confidence: 78%
“…Our previous work showed IL-1-mediated astrocyte Fas ligand expression and subsequent caspase activation in surrounding neurons in vitro (Deshpande et al, 2005). We have also shown the effects of IL-1 and HIV-1 gp120, leading to CD38 upregulation in primary astrocyte cultures (Banerjee et al, 2008) and increased CD38 mRNA and protein expression in HIVE brain (Kou et al, 2009). IL-1-activated astrocytes are known to release cytokines like IL-6 and chemokines like CCL2, CXCL8 and RANTES (Lee and Aarhus, 1993;Zhao and Brinton, 2004;Sharma et al, 2007).…”
Section: Neuroinflammation During Hive and Astrocytesmentioning
confidence: 84%
See 1 more Smart Citation